The Effectiveness of Puzzle Games as a Learning Media for Teaching Simple Present Tense in a Junior High School - Bremas Aluth Maulidian Syah (Proceedings Series on Social Sciences & Humanities, 2024)
This study aims to determine whether there is a significant difference in students’ understanding of the simple present tense between those taught using puzzle games and those who are not. This quasi-experiment involved a sample of 60 eighth-grade students divided into control and experimental groups, each consisting of 30 students. Data were collected from pre-test and post-test scores administered to both groups. After analyzing the data, the researcher found it was not normally distributed, necessitating a non-parametric statistical test, the Mann-Whitney test, for hypothesis testing. The results indicated that the significance of the Mann-Whitney test was greater than 0.05, suggesting no significant difference in the understanding of the simple present tense between students taught with puzzle games and those not. The researcher hypothesizes that the scope of the material, insufficient vocabulary knowledge, and poor understanding of parts of speech may contribute to the ineffectiveness of puzzle games in teaching the simple present tense.